Rural Women Oyster (Crassostrea Gasia) Post-Harvest Activities in Kalabari Kingdom of Rivers State, Nigeria - C.O. A, Elenwa; J.E., Allen (Journal of Home Economics Research, 2024)
The study focused on rural women’s oyster (Crassostrea gasia) post-harvest activities in Kalabari kingdom of Rivers State, Nigeria. A total of 90 women were purposively selected from the area. Data were collected through the use of interview schedule. Data were analyzed using frequency, percentage, mean scores, ordinary least square (OLS) multiple regression and cost-revenue ratio. Findings show that majority (35.7%) were between 31 -40years, were married (47.7%), had formal education (76.2%), had an income level between N26,000 – N39,000 (33.3%), and household size of 5-8 persons(37.3%) and have been in oyster harvesting activities between 11-15 years (33.3%). Levels of women involvement in oyster harvesting were: removing oyster shells and selling ( =2.93), cutting oysters from mangrove tree ( =2.82) and roasting of oysters as a means of preservation ( =2.60). Oyster harvesting from mangrove (whole sale) had highest profit of N45, 500 per week. The major constraints to Oyster harvesting were low fund ( =2.82), water pollution by oil activity ( =2.92) and water pollution by human activity ( =2.60). The study recommends that water pollution by oil and human activities should be tackled by the government by monitoring illegal processing of crude oil in the area.